Exact algorithms for the robust uncapacitated multiple allocation p-hub median problem - Ghaffarinasab, Nader (Optimization letters, 2022)
This paper addresses the robust uncapacitated multiple allocation p -hub median problem where the demand traffic between origin-destination pairs are subject to uncertainty. The employed robust optimization approach adjusts the level of conservatism by using a parameter called the budget of uncertainty . A mixed-integer programming linear formulation is proposed for the problem and two exact solution procedures based on Benders decomposition are developed to solve large-scale instances of the problem. Extensive computational experiments are conducted to study the effect of incorporating uncertainty into the problem and to evaluate the performance of the proposed mathematical models as well as the solution algorithms.